Peningkatan Pengetahun dan Pengeloaan Dasar Keuangan bagi Pelaku Usaha di Destinasi Wisata Wae Bobok - Agus Wahyudi; Ni Wayan Noviana Safitri; Liesiana Kurniawati; Ni Made Dwita Ratnaningsih; Ludgardis Deliman (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2022)
Diploma IV-Tax Accounting Study Program at the eLBajo Commodus Polytechnic has duties and responsibilities to the community to carry out the Tri Dharma of higher education, one of which is community service. Therefore, the community service team consisting of lecturers from the Diploma IV-Tax Accounting Study Program at the eLBajo Commodus Polytechnic provided socialization in the financial sector to increase knowledge in financial management for managers and business actors at Wae Bobok Tourism Destinations. The importance of this community service is because there are still deficiencies in financial management, ranging from human resources who do not have competence in financial management to inadequate supporting facilities and infrastructure. implementation of Community Service activities DIV-Tax Accounting Study Program which was attended by 20 participants consisting of shop owners or stalls as well as managers of tourist attractions at Wae Bobok Tourism Destinations, as well as other village communities who are interested in participating. Participants also hope that this activity can be continued with regular sustainability training and mentoring.